Fbxl13 regulates centrosome homeostasis and migration through ubiquitin mediated proteolysis - Fung, E (2017)
Fbxl13 (F-box and leucine-rich repeat protein 13) is an orphan F-box protein. Fbox proteins are a family of substrate-targeting specificity factors for the SCF superfamily of E3 ubiquitin ligases. Since their discovery, many F-box proteins have been shown to have oncogenic and tumour suppressive roles. The importance of Fbxl13 itself in tumourigenesis is reflected in several genome-wide shRNA screens. Fbxl13 depletion in human cancer cells correlates with increased ionising radiation sensitivity and increased genomic instability. Furthermore, Fbxl13 depletion reduces proliferation in mouse embryonic epidermis. Conversely, Fbxl13 amplification is frequently observed in several cancer patient cohorts. However, the main function of Fbxl13 is unknown and its biochemical mechanism of action remains uncharacterised. The aim of this study was to identify the interactors, substrates, and functions of Fbxl13, in order to elucidate its role in tumourigenesis. In this study, I identify and validate Fbxl13 interactors Centrin-2, Centrin-3, Cep152, and Cep192. I show that Fbxl13 is enriched at the centrosome, and present evidence that Fbxl13 targets Cep192-3 for ubiquitin mediated proteolysis. In line with this, Fbxl13 overexpression downregulated centrosomal Cep192 and γ-tubulin, and disrupted the microtubule nucleation activity at the centrosome. Finally, Fbxl13 amplification in U2OS cells is associated with increased cell motility. Thus, we propose that Fbxl13 is a novel regulator of centrosome microtubule nucleation activity.